PERAN BANK SAMPAH DALAM MENINGKATKAN EKONOMI MASYARAKAT PERSPEKTIF EKONOMI ISLAM (STUDI KASUS BANK SAMPAH MOJOREJO ASRI) - Linawati, Linawati; Meilana, Putri Bibit (Investama : Jurnal Ekonomi dan Bisnis, 2025)
Waste is one of the main factors causing environmental problems that are still ongoing today. The imbalance between the volume of waste production and its management capacity causes waste accumulation. The presence of waste banks provides an alternative solution for the community in an effort to reduce this accumulation, namely by managing waste that previously had no use value into goods that have economic value. This study aims to examine the extent to which the role of Mojorejo Asri Waste Bank in improving the economic welfare of the community, in terms of Islamic Economics. The approach used in this research is a qualitative method, with the utilization of primary and secondary data obtained through observation techniques, in-depth interviews, and documentation of direct sources. The results showed that the existence of Mojorejo Asri Waste Bank contributed to helping fulfill the economic needs of the community, although this contribution has not been able to cover all needs as a whole. The waste management mechanism is carried out through the participation of the community who collect waste and submit it directly to the waste bank or through officers who make pick-ups. From an Islamic perspective, the buying and selling practices carried out by waste banks are considered valid or permissible. In addition, the principles applied in waste bank operations are in line with the concept of human responsibility as khalifah on earth.